Climate change mitigation and ecosystem services: a stochastic analysis - Thomas S. Lontzek; Daiju Narita (Kiel Institute for the World Economy (IfW), 2010)
Degradation of ecosystem services may be a major component of climate change damage, and incorporation of this factor could significantly alter the significance of uncertainty in climate-economy modeling. However, this aspect has been little investigated by economic analyses of climate change and uncertainty. We apply standardized numerical techniques of stochastic optimization to this research question. The model results show that the effects of uncertainty are different with different levels of agent's risk aversion. Also, uncertainty exhibits different effects on mitigation policy and capital investment according to the availability of ecosystem services. Importantly, both the risk aversion and the availability of ecosystem services can change the effects of uncertainty on mitigation not only in level but also in sign. In other words, mitigation could both increase and decrease with climatic uncertainty. The model would provide hints for policymaking in finding a balance between economic growth, climate protection, and the conservation of ecosystems.
Keywords: C63; Q54; D81; 330; Climate change; decision making under uncertainty; stochastic control; renewable resource; ecosystem services